2021
DOI: 10.3390/nu13082691
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Children and Maintaining Food Service Operations during COVID-19: A Mixed Methods Investigation of Implementation and Financial Challenges

Abstract: The United States Department of Agriculture (USDA) National School Lunch and Breakfast Programs are critical for the health and food security of U.S. schoolchildren, but access to these programs was disrupted by COVID-19 pandemic-related school closures in spring 2020. While temporary policy changes to the programs enabled school food authorities (SFAs) to pivot towards distributing meals throughout their communities instead of within school buildings, SFAs faced complex challenges during COVID-19 with minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 23 publications
4
44
0
2
Order By: Relevance
“…Travel was often a challenge for them (39), despite substantial efforts by school food authorities to make meal acquisition as easy as possible. (29,37) In contrast, the effort required for households to receive P-EBT was relatively low, in that cards were automatically mailed to families of children known to be eligible and could be used to buy food at any store accepting EBT. It is worth noting that a recent report suggested that the high P-EBT coverage seen when schools were uniformly closed may be difficult to maintain during periods when the extent of school closures varies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Travel was often a challenge for them (39), despite substantial efforts by school food authorities to make meal acquisition as easy as possible. (29,37) In contrast, the effort required for households to receive P-EBT was relatively low, in that cards were automatically mailed to families of children known to be eligible and could be used to buy food at any store accepting EBT. It is worth noting that a recent report suggested that the high P-EBT coverage seen when schools were uniformly closed may be difficult to maintain during periods when the extent of school closures varies.…”
Section: Discussionmentioning
confidence: 99%
“…(42) Prior research has shown that delivery of grab-and-go school meals is more costly compared to providing regular school meals on-site when schools are open. (29).…”
Section: Discussionmentioning
confidence: 99%
“…More than 15 years after the SFPs inception, a rigorous independent program evaluation is necessary, as is the norm elsewhere [ 58 , 59 ]. Not until 2015 did the Ministry of Health issue guidelines on children’s nutrition in educational frameworks.…”
Section: Main Textmentioning
confidence: 99%
“…At the same time, many of the existing challenges in implementing school nutrition programs, including staffing issues and limited capacity, 15 were magnified during the pandemic. School food authorities had to adapt to rapidly changing conditions without having additional revenue to compensate for additional labor, food, and equipment 16 …”
Section: School Nutrition During the Covid‐19 Pandemicmentioning
confidence: 99%
“…School officials may choose to share information about community programs when school nutrition programs are not available, as was the case in several Ohio districts. In addition to supporting families, school districts can use social media to express appreciation for school employees, who have reported feeling underappreciated during the pandemic 16 . Moving out of the pandemic, school officials should continue to provide information for families who are eligible for the NSLP and SBP.…”
Section: Implications For School Healthmentioning
confidence: 99%